JUMPA Vol.2 No.2 Juni 2015 PENGARUH SIZE FIRM, TIPE INDUSTRI, PROFITABILITAS, KINERJA LINGKUNGAN DAN MEDIA EXPOSURE TERHADAP CORPORATE SOCIAL DISCLOSURE RESPONSIBILITY: PENGARUH SIZE FIRM, TIPE INDUSTRI, PROFITABILITAS, KINERJA LINGKUNGAN DAN MEDIA EXPOSURE TERHADAP CORPORATE SOCIAL DISCLOSURE RESPONSIBILITY - Dwi Retnoningtyas H Arista Group (Jurnal Manajemen dan Perbankan (JUMPA), 2015)
The objective of this research is to examine empirically whether the size firm, type of industry, profitability, environmental performance, and media exposure are giving effect to Corporate Social Responsibility Disclosure in manufacturing companies, which listed at Indonesia Stock Exchange. The sample of this research is manufacturing companies, which listed at Indonesia Stock Exchange (IDX) on 2011-2013. The number of samples used 32 companies that have been selected based on some sample selection criteria. The selection of the samples is using purposive sampling. Then, those kinds of elements are tested using multiple regression. The result of this research have been identified that there are significant effect between size firm (UP) and type of industry (TI) to corporate social responsibility disclosure. Meanwhile profitability (PROFIT), environmental performance (KL) and media exposure (ME) are not giving significant effect to corporate social responsibility disclosure on manufacturing companies, which listed at Indonesia Stock Exchange (IDX).